2016
DOI: 10.1016/j.anclin.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Autoregulation and Dysautoregulation

Abstract: The aim of this article is to provide an up-to-date review of the state-of-the-art in cerebral autoregulation, particularly as it may relate to the clinician scientist whose expertise is in the area of neuroscience in anesthesia and critical care. Topics covered range from biological mechanisms, methods used for assessment of autoregulation, effects of anesthetics, role in control of cerebral hemodynamics in health and disease such as traumatic brain injury where dysregulation is evident, and emerging areas su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
160
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(185 citation statements)
references
References 74 publications
2
160
0
4
Order By: Relevance
“…Comparing with healthy controls, we found that dCA on both the ipsilateral hemisphere and the contralateral hemisphere were impaired in AIS patients. Consistently with our study, previous researches also reported bilateral impaired CA in the acute stroke [28,29]. The mechanism of this trans-hemispheric communication may be diaschisis where there is distant functional depression due to the effects of loss of axons (mainly facilitatory) arising at the site of the lesion and, in the case of the cerebral hemispheres, these may synapse with neurons in the contralateral hemisphere via the corpus callosum [30].…”
Section: Choosing Dca As the Markersupporting
confidence: 90%
“…Comparing with healthy controls, we found that dCA on both the ipsilateral hemisphere and the contralateral hemisphere were impaired in AIS patients. Consistently with our study, previous researches also reported bilateral impaired CA in the acute stroke [28,29]. The mechanism of this trans-hemispheric communication may be diaschisis where there is distant functional depression due to the effects of loss of axons (mainly facilitatory) arising at the site of the lesion and, in the case of the cerebral hemispheres, these may synapse with neurons in the contralateral hemisphere via the corpus callosum [30].…”
Section: Choosing Dca As the Markersupporting
confidence: 90%
“…46 This variability may be further elevated for CBF, as sex hormones are involved in numerous aspects of blood flow regulation. 47 Interestingly, the male and female control groups showed no significant differences in CBF variability within the temporal lobes, making it unlikely that the greater variability in female CBF is due to hormonal differences at the time of imaging. Supplementary analyses, which compared athletes with a single concussion to those with multiple concussions, demonstrated that elevated CBF variability in the female HOC group also may be related to clinical history.…”
Section: Sex Differences In Cbf After Concussion 1201mentioning
confidence: 91%
“…Further adding to the ischemic conditions, TBI is also associated with impaired pressure autoregulation or loss of cerebral vascular response to arterial blood pressure changes (Engelborghs et al, 2000;Lang et al, 2003;Lewelt, Jenkins, & Miller, 1980;Rodriguez et al, 2018). Autoregulation normally acts to preserve proper CBF when the cerebral perfusion pressure changes (Armstead, 2016;Castro, Azevedo, & Sorond, 2018). However, cerebral ischemia can be more adverse in terms of duration and intensity when this CBF maintenance system is damaged.…”
Section: Ischemiamentioning
confidence: 99%